Information and Communication Technologies in Tourism 2019 : Proceedings of the International Conference in Nicosia, Cyprus, January 30–February 1, 2019 / [Editors] Juho Pesonen; Julia Neidhardt - Neidhardt, Juliaeditors
Includes bibliographical references and index